330 Community Health Worker integration as a culturally competent component of patient-centered wellness - Antonette Francis-Shearer; Amber Singleton; Karla McCants; Danette M; Jolly; Maggie Cheyenne; Garland; Katherine Bolanos; Clinic Luke; Mueller; Martha I; Arrieta; et al. (Journal of Clinical and Translational Science)
Objectives/Goals: 1) Discuss process of pilot integration of Community Health Worker (CHW) services as a component of patient-centered healthcare service delivery in 3 clinic models. 2) Summarize profiles of patients who self-select to utilize CHW services. 3) Discuss social determinants of health impacts of underserved and historically marginalized populations. Methods/Study Population: The priority population consists of individuals living in Mobile AL at or below poverty level. USA Health Center for Healthy Communities (CHC) piloted the integration of CHW services at USA Health Stanton Road Clinic (SRC), at USA Student Run Free Clinic (SRFC), and as part of a Medi Hub Outreach Clinic with the historically underserved MOWA Choctaw native American population. SRC is a high-utilization clinic for uninsured or underinsured patients across the breadth of the Gulf Coast. The other 2 sites serve similar clientele. Social determinants of health (SDOH) screenings at intake facilitate CHW referral for a clients’ unique needs for support at healthcare or social care agencies. Referral summaries can then be used to guide planning, community collaborating partner intervention, and clinical quality certification, Results/Anticipated Results: Results include identification of referrals process by which CHWs are able to provide culturally competent support to persons accessing healthcare services at the 3 clinic models identified. Identification of top SDOH needs that preclude access to care among the patients served during a 24-month pilot period, e.g., (i) housing insecurity, (ii) food insecurity, (iii) transportation, (iv) health Ins, and (v) pharmacy access and payment assistance. Discussion of beneficial impacts for health care service delivery with other members of the multidisciplinary clinical teams as recorded referrals can be used to guide planning, clinic certification efforts Discussion/Significance of Impact: Patient utilization of CHW services though self-selective offers opportunities for equity in access to care services from direct SDOH impacts, where CHWs act as responsive resource coordinators within the multi-disciplinary service delivery team.